ممارسة النشاط الزراعي في مقاطعة نوميديا من خلال نصوص النقيشات اللاتينية - بوشارب, سهيلة (University of Eloued جامعة الوادي, 2021)
ملخص: يعالج موضوع ممارسة النشاط الزراعي في مقاطعة نوميديا من خلال نصوص النقيشات اللاتينية اشكالية رئيسة تتمحور حول طبيعة المهن و الحرف المتعلقة بممارسة النشاط الزراعي و علاقتها ببعض فئات المجتمع النوميدي و كذا بطبيعة المنطقة من الناحية الجغرافية بهدف الكشف عن الواقع الاقتصادي للطبقات الدنيا فيه لاعادة الاعتبار لأصحاب الحرف و المهن البسيطة لأنها ذات فعالية اقتصادية، و قد توصلت إلى مجموعة من النتائج نذكر منها: مدى تمسك أفراد الطبقات البسيطة بالأرض وكل ما يتعلق بالنشاط الزراعي عن طريق ممارستهم لمختلف الحرف الزراعية على الرغم من صعوبتها، تأثر النوميديون ببيئتهم الجغرافية و محاولتهم التأقلم معها.Abstract: The issue of practicing agricultural activity in the province of Numidia deals with through the texts of Latin inscriptions a major problem centered on the nature of the professions and crafts related to the practice of agricultural activity and its relationship to some groups of Numidian society, as well as the nature of the region in terms of geography, with the aim of revealing the economic reality of the lower classes in it to restore consideration to the owners of crafts And simple professions because they are economically effective, and they have reached a set of results, including: the extent to which members of the simple classes adhere to the land and everything related to agricultural activity through their practice of various agricultural trades despite its difficulty, the Numidians were affected by their geographical environment and their attempt to adapt to it.